The Role Of Financial Wellbeing In The Halal Industry: A Systematic Literature Review - Anita Ismail; Farah Laili Muda @ Ismail; Sharbani Harun; Nur Ainna Ramli; Hisham Sabri; Fitriah Susilowati (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA